MORAL VALUES IN FREDERICK DOUGLASS' NARRATIVE OF THE LIFE OF FREDERICK DOUGLASS, AN AMERICAN SLAVE (1845) - Dwiputri, Freischa; Oroh, Elizabeth Z.; Kamagi, Sarah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this research is to reveal the moral values in Frederick Douglass’ Narrative of the Life of Frederick Douglass, an American slave (1845). It is done to show the types of moral values that exist in the novel. This research is qualitative research since the data gathered are in the form of words rather than number. In analyse the data; the writers employ a mimetic method, the study only focused no moral values in Frederick Douglass. Based on the results of the discussion show that there are eight kinds of moral values such as Living life full of Steadfastness, A good Cooperativeness to achieve a goals, Bravery to take a risk, Sympathetic with others, Stick firmly to Trustworthiness, Thankfulness for the things that are owned in Life, Be kind to everyone and Have Limitless Love and Affection.